Fiber diameter as design parameter for tailoring the macroscopic shape-memory performance of electrospun meshes. (April 2021) - Sauter, Tilman; Kratz, Karl; Heuchel, Matthias; Lendlein, Andreas
Abstract: Fibrous shape-memory polymer (SMP) scaffolds were investigated considering the fiber as basic microstructural feature. By reduction of the fiber diameter in randomly oriented electrospun polyetherurethane (PEU) meshes from the micro- to the nano-scale, we observed changes in the molecular orientation within the fibers and its impact on the structural and shape-memory performance. It was assumed that a spatial restriction by reduction of the fiber diameter increases molecular orientation along the orientation of the fiber. The stress-strain relation of random PEU scaffolds is initially determined by the 3D arrangement of the fibers and thus is independent of the molecular orientation. Increasing the molecular orientation with decreasing single fiber diameter in scaffolds composed of randomly arranged fibers did not alter the initial stiffness and peak stress but strongly influenced the elongation at break and the stress increase above the Yield point. Reduction of the single fiber diameter also distinctly improved the shape-memory performance of the scaffolds. Fibers with nanoscale diameters (< 100 nm) possessed an almost complete shape recovery, high recovery stresses and fast relaxation kinetics, while the shape fixity was found to decrease with decreasing fiber diameter. Hence, the fiber diameter is a relevant design parameter for SMP. Graphical abstract: Unlabelled Image Highlights: Meshes with randomly oriented shape-memory fibers (diameters 2.3, 1.0, 0.3 and 0.08 μm) were fabricated. The fiber diameter has been identified as design parameter for the shape-memory performance. An engineering approach to estimate the molecular orientation, depending on strain and fiber diameter, was accomplished. Higher molecular orientation led to strong increase in shape-recovery ratio, maximum recovery stress and shape recovery speed. Transition of micron- to submicron-sized fiber diameters indicates a threshold with strongly increased molecular orientation.